Oligarchic Power Representation in Documentary Film Pesta Oligarki: Representasi Kekuatan Oligarki dalam Film Dokumenter Pesta Oligarki - Dwi Cahyo Nugroho; M Andi Fikri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Oligarchy remains a significant issue in Indonesian political and economic discourse, particularly within democratic and electoral processes. Specific Background: The documentary film Pesta Oligarki produced by Watchdoc Documentary presents socio-political phenomena related to elite domination during the 2024 Indonesian elections. Knowledge Gap: Academic examination of how oligarchic practices are symbolically represented through documentary visual narratives remains limited. Aims: This study analyzes the representation of oligarchic practices in the film using Charles Sanders Peirce’s semiotic framework. Results: Six major scenes illustrate land evictions, legislative control by political parties, political image construction, state repression, presidential nomination restrictions, and opposition co-optation, demonstrating oligarchic penetration into political, legal, and social structures. Novelty: This research applies Peirce’s triadic semiotic model to interpret oligarchic symbolism within Indonesian political documentary cinema. Implications: The findings highlight documentary film as a medium of social criticism and political education that encourages public critical awareness of democratic processes and power relations in Indonesia. Highlights: Visual Narratives Reveal Systemic Elite Domination Across Governance, Law, and Public Policy Processes. Symbolic Cinematic Elements Portray Democracy as Structurally Controlled by Concentrated Political and Economic Actors. Documentary Storytelling Functions as a Critical Medium for Public Political Awareness and Reflection. Keywords: Oligarchy, Documentary Film, Semiotics, Political Communication, 2024 Elections